Bhutan : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
This paper discusses Bhutan's Poverty Reduction Strategy Paper (PRSP). The Royal Government of Bhutan has initiated the PRSP process as part of broader ongoing efforts to combat poverty. The main objective of the PRSP process is to strengthen the strategic framework for poverty reduction, improve donor coordination, and build support for new initiatives in public expenditure management and poverty monitoring and evaluation. The envisaged process builds directly on the Ninth Five-Year Plan (Ninth Plan).